RETRACTED ARTICLE: Multivariate optimization of removing of cobalt(II) with an efficient aminated-GMA polypropylene adsorbent by induced-grafted polymerization under simultaneous gamma-ray irradiation - Fatemeh Maleki; Mobina Gholami; Rezvan Torkaman; Meisam Torab-Mostaedi; Mehdi Asadollahzadeh (Scientific Reports)
Abstract Nowadays, radiation grafting polymer adsorbents have been widely developed due to their advantages, such as low operating cost, high efficiency. In this research, glycidyl methacrylate monomers were grafted on polypropylene polymer fibers by simultaneous irradiation of gamma-ray with a dose of 20 kGy. The grafted polymer was then modified using different amino groups and tested for adsorption of cobalt ions in an aqueous solution. Finally, the modified polymer adsorbent with a high efficiency for cobalt ions adsorption was synthesized and tested. Different modes of cobalt ions adsorption were tested in other adsorption conditions, including adsorption contact time, pH, different amounts of adsorbent mass, and different concentrations of cobalt ions solution. The adsorbent structure was characterized with FT-IR, XRD, TG and SEM techniques and illustrated having an efficient grafting percentage and adsorption capability for cobalt removing by batch experiments. The optimum conditions were obtained by a central composite design: adsorbent mass = 0.07 g, initial concentration = 40 mg/L, time = 182 min, and pH = 4.5 with ethylenediamine as a modified monomer and high amination percentage. Kinetics and equilibrium isotherms observation described that the experimental data followed pseudo-second-order and Langmuir models, respectively. The maximum adsorption capacity from Langmuir isotherm capacity is obtained equal to 68.02 mg/g.